2018
DOI: 10.4236/psych.2018.95073
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Empowerment: Users and Professionals in Psychiatric Care before and after Mindfulness Treatment

Abstract: The current study had two purposes, namely for the first time to investigate the degree of psychological empowerment (PE) before and after treatment with Mindfulness-Based Cognitive Therapy, and also for the first time to compare mental health users with professional healthcare providers in psychiatry in this respect. PE encompasses the processes that allow people greater control over their lives and to develop critical awareness of their sociopolitical environments. Participants were 14 mental health users (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Michelsen et al argues that mindfulness-based therapy contributes to psychological empowerment and self-compassion, which was another result of the present study. 25 Mindfulness-based meditation techniques (yoga, etc.) change how women perceive sexuality and gender roles.…”
Section: Discussionmentioning
confidence: 99%
“…Michelsen et al argues that mindfulness-based therapy contributes to psychological empowerment and self-compassion, which was another result of the present study. 25 Mindfulness-based meditation techniques (yoga, etc.) change how women perceive sexuality and gender roles.…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of resource theory, psychological empowerment is considered by many researchers to be a resource that is relevant for occupational goals [ 43 , 44 ], while dispositional mindfulness is believed to enhance an individual's ability to explore and utilize resources [ 27 , 28 ], suggesting a potential association between dispositional mindfulness and psychological empowerment. Studies have also found that participants' psychological empowerment can be enhanced via mindfulness training [ 45 ]. Some studies have shown that dispositional mindfulness can positively correlate with an individual's sense of meaning of work [ 46 ], which is an important component of psychological empowerment.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…The investigation of literature of mindfulness and its influence on psychological empowerment unveils a complex interplay. In the field of mental health and psychiatry, research by Michelsen et al (2018) found that Mindfulness-Based Cognitive Therapy (MBCT) significantly bolsters psychological empowerment among both mental health service users and professionals. This research underscores the dual advantages of mindfulness in enhancing mental well-being, interpersonal connections, and self-compassion.…”
Section: Role Of Mindfulness On Psychological Empowermentmentioning
confidence: 99%